HISTORY OF ORIGIN OF THE UZBEK TERM - Turayeva Matluba (Galaxy International Interdisciplinary Research Journal, 2021)
In Uzbekistan, the remains of dozens of semi - basement settlements such as high Paleolithic monuments-puddles, ostrich, Siyobcha, Takalisoy, Khujamazgil, Achchisoy and Sari Ark were found and studied. Of these, stone scrapers, chisels, knife-shaped stone weapons, stone tools, a needle made of bone, a mustache, a fork and a pendant, a tuya, a bug and a pig bone are recorded.